44 The Form of Selenium in Free-Choice Vitamin-Mineral Mixes Affects the Percentage of Circulating Neutrophils and Lymphocytes in Beef Calves Subjected to Combined Weaning and Shipping Events. (1st March 2018) - Jia, Y; Adams, A A; Burris, W R; Bridges, P; Matthews, J C
Abstract: The goal of this trial was to determine if the form of selenium (Se) in free-choice vitamin-mineral mixes affected the differential count of circulating leukocytes and serum parameters of beef calves stressed by combined weaning and shipping events. Predominantly-Angus suckling steer (BW = 297 ± 17 kg) and heifer (BW = 253 ± 33 kg) calves were randomly selected from herds of fall-calving cows grazing endophyte-infected tall fescue pasture and consuming vitamin-mineral mixes that contained 35 ppm Se as either an inorganic form (ISe, sodium selenite) or a 1:1 blend (MIX) of ISe and organic (SEL-PLEX) forms. Calves (9 ISe steers, 9 MIX steers, 9 ISe heifers, 12 MIX heifers) were weaned (d 0) and immediately shipped 900 mi (18 h). Post-shipping, all calves were penned by Se treatment and fed a corn and cotton-seed hull-based diet and had ad libitum access to their respective Se treatments. On d 0, the effect of Se treatment on whole blood Se within steer and heifer groups was assessed using the PROC GLM procedure of SAS. For both steer and heifer groups, blood Se was greater (P < 0.05) in MIX than ISe calves. The PROC MIXED procedure of SAS was used to assess the effect of Se treatment on complete blood cell counts and serum parameters on d 0, 1 (immediately after shipping), 2, 4, and 11 relative to weaning/shipping within steer and heifer groups. Fisher's protected LSD procedure was used to separate treatment means. Se treatment did not affect (P ≥ 0.10) serum cortisol in steer or heifer groups. However, the percentage of neutrophils increased (P < 0.01) for both Se treatments after weaning and shipping (d 1) and was less (P < 0.01) in MIX steer and heifer groups throughout the trial. In contrast, the percentage of lymphocytes decreased (P < 0.01) for both Se treatments on d 1 and was greater (P < 0.01) in MIX steer and heifer groups from d 0 to d 11. Se treatment did not affect (P > 0.05) total leukocyte count or the percentage of monocytes in steer and heifer groups. Blood urea nitrogen was less (P < 0.01) in MIX than ISe steer and heifer groups from d 0 to d 11. In conclusion, form of Se affected the percentage of circulating neutrophils and lymphocytes and N metabolism of steers and heifers subjected to combined weaning and shipping events.